Genome-wide characterization of copy number variations in Nagami Mithun (Bos frontalis) using whole-genome resequencing - Bendangkokba Kichu; Harshit Kumar; Rajkrishna Mondal; Kuluve Chotso; J. K. Chamuah; S. S. Hanah; Girish Patil Shivanagowda (Mammalian Genome, 2026)

Gas chromatography–mass spectrometry analysis of the secondary metabolites produced by Bacillus paramycoides BOK01 and Microbacterium barkeri BPATH02 and investigation of their antifungal activity against tea pathogens - Pranay Raj; Harshit Kumar Sharma; Venkatesan Selvaraj; Abhay Kumar Pandey (Antonie van Leeuwenhoek, 2026)

Biophysical and biochemical mechanisms underlying resistance in Brassica juncea against mustard aphid, Lipaphis erysimi - Harshit Mishra; Kamal Ravi Sharma; Sameer Kumar Singh (International Journal of Tropical Insect Science, 2026)

Carbon loaded zinc sulfo-oxide (C@Zn(S + O)) composite for efficient and rapid adsorptive removal of Congo red dye from wastewater: optimization, thermodynamics, isothermal and kinetics analysis - Harshit Gupta; Shrawan Kumar; Ria Baliyan; Nahar Singh (Environmental Science and Pollution Research, 2026)

Pathological and molecular characterization identified Muyocopron laterale as a new pathogen causing brown leaf spot disease of tea in India - Harshit Kumar Sharma; Pranay Raj; Sajeewa S. N. Maharachchikumbura; Abhay Kumar Pandey (Journal of Plant Diseases and Protection, 2026)

Effects of heading back on leaf nutrients, flowering, physiological and fruit-related traits in mango (Mangifera indica L.) cv. Amrapali - Harshit Kumar; Manish Srivastav; Kanhaiya Singh; A. Nagaraja; S. Gopala Krishnan; Pandey Rakesh; Shruti Shethi; V. K. Sharma; Gulshan Kumar; Prabhanjan Rane; Hansraj Meena (Vegetos, 2026)

Effect of Tree Age on Leaf Nutrient, Flowering, Physiological and Fruit-Related Traits in ‘Amrapali’ Mango (Mangifera indica L.) Under an Intensive Planting System - Harshit Kumar; Manish Srivastav; Gulshan Kumar; Prabhanjan Rane; Hansraj Meena; Kanhaiya Singh; A. Nagaraja; Gopala Krishnan S.; Rakesh Pandey; Shruti Shethi; V. K. Sharma (Applied Fruit Science, 2026)

A comprehensive review on Mithun (Bos frontalis): a keystone species in sustainable livelihoods of the eastern Himalayas and Indo-Burma region - Youngmei Arolim; Harshit Kumar; Sapunii Stephen Hanah; Tapas Kumar Biswas; Kathiravan Periasamy; Kuluve Chotso; Jayanta Kumar Chamuah; Girish Patil Shivanagowda (Tropical Animal Health and Production, 2026)

Inter-hemispheric climate linkages and monsoonal controls on the Arabian Sea surface temperatures - Harshit Singh; Arun Deo Singh; Aindabi Maitra; Bandan Kumar; Shubham Tripathi; Pradyumna Singh; Shivranjan Kumar Bharti (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Zinc Peroxide-based Carbon Composite for the Removal of Highly Toxic Insecticide Acetamiprid from Water - Shrawan Kumar; Harshit Gupta; Arvind Gautam; Nahar Singh (Water, Air, & Soil Pollution, 2026)

Development of a visual assay for Mithun (Bos frontalis) meat authentication using polymerase spiral reaction (PSR) - Moon Moon Mech; Hanumant Singh Rathore; Arockiasamy Arun Prince Milton; Nagappa Karabasanavar; Kandhan Srinivas; Sabia Khan; Zakir Hussain; Vikram Ramesh; Harshit Kumar; Samir Das; Sandeep Ghatak; Girish Patil Shivanagowda (Food Control, 2026)

Role of CRISPR in bioremediation of heavy metal(loid): a breakthrough in environmental biotechnology - Harshit Mangal; Shivangi Mathur; Sunil Kumar; Anurag Chaurasia; Rajiv Ranjan (World Journal of Microbiology and Biotechnology, 2026)

Impact of Micronutrients on Flowering, Yield, and Fruit Quality Attributes of Strawberry (Fragaria × ananassa Duch) cv. Camarosa Under Open Field Conditions - Yogendra Singh; Govind Gupta; Ujwal Virkhare; Mukul Kumar; Prajwal Nimbulkar; Suman Kumari; Yogita Chouhan; Harshit Jangid; Suresh Chandra Gurjar; Om Prakash Lodha; Deepak Kher (Applied Fruit Science, 2025)

First report of Curvularia alcornii causing leaf blight disease on tea (Camellia sinensis) in North Bengal, India - Abhay Kumar Pandey; Harshit K. Sharma; Abhishek Kumar; Pranab Dutta (Journal of Plant Pathology, 2025)

Changes in the upper water-column structure of the eastern equatorial Indian Ocean during 12.8–4.7 ka - Pradyumna Singh; Arun Deo Singh; Shubham Tripathi; Harshit Singh; Abhayanand Singh Maurya; Sushant Suresh Naik; Rakesh Kumar (Quaternary International, 2025)

Synergistic effect of molybdenum and Rhizobium on growth and yield of vegetable cowpea (Vigna unguiculata (L.) Walp.) - Monu Kumari; Nitin B. Patel; Kapil Dev Ameta; Akshay Kumar Yogi; Harshit Kumar; Ayushi Jain (Vegetos, 2025)

Pesticide-driven antimicrobial resistance in water bodies: insights on environmental concerns, health implications and mitigation strategies - Vishwajeet Sonkar; Harshit Devtalla; Shakti Kumar (Environmental Geochemistry and Health, 2025)

Phylogenetic reassessment and epitypification of Exobasidium vexans causing blister blight of tea - Ganga Devi Sinniah; Dalawellage Chanuka Madushanka Kulatunga; Abhay Kumar Pandey; Harshit Kumar Sharma; Nelanka Priyadarshani Colombage; Dhanushka Udayanga (Australasian Plant Pathology, 2025)

Computational investigation of antiviral peptide interactions with Mpox DNA polymerase - Harshit Tiwari; Ashal Ilyas; Pankaj Kumar Rai; Shashank Upadhyay; Subhomoi Borkotoky (In Silico Pharmacology, 2025)

Genetic parameters of body weight traits in Mithun (Bos frontalis) using animal model - Harshit Kumar; Ashish Yadav; Sapunii Stephen Hanah; L. Sunitibala Devi; Kobu Khate; Girish P.S. (Tropical Animal Health and Production, 2024)

Bottom-up approach to explore alpha-amylase assisted membrane remodelling - Harshit Kumar; Sayar Mandal; Reena Yadav; Suhasi Gupta; Hemraj Meena; Mayur Kadu; Rajni Kudawla; Pratibha Sharma; Indu Pal Kaur; Subhabrata Maiti; John H. Ipsen; Tripta Bhatia (Chemistry and Physics of Lipids, 2024)

Reversing the damage: ecological restoration of polluted water bodies affected by pollutants due to anthropogenic activities - Harshit Chawla; Santosh Kumar Singh; Anil Kumar Haritash (Environmental Science and Pollution Research, 2023)

First report of whole genome sequence of septicemic Pasteurella multocida serovar B:2 ‘Soron’ strain isolated from swine - Harshit Verma; Mayank Rawat; Rishendra Verma; Ravi Gandham; Ashok Kumar Tiwari; Raja Ishaq Nabi Khan; Manas Ranjan Praharaj; Emily Smith (Brazilian Journal of Microbiology, 2023)

Air pollution prediction system using XRSTH-LSTM algorithm - Harshit Srivastava; Santos Kumar Das (Environmental Science and Pollution Research, 2023)

Anaerobic digestion as a tool to manage eutrophication and associated greenhouse gas emission - Amit Singh; Mohit Singh Rana; Harshit Tiwari; Manoj Kumar; Sarthak Saxena; Vishal Anand; Sanjeev Kumar Prajapati (Science of The Total Environment, 2023)

Allelopathic effect of benzoic acid (hydroponics root exudate) on microalgae growth - Harshit Tiwari; Sanjeev Kumar Prajapati (Environmental Research, 2023)

Unraveling genetic admixture in the Indian crossbred cattle by different approaches using Bovine 50K BeadChip - Dhan Pal; Manjit Panigrahi; Supriya Chhotaray; Harshit Kumar; Sonali Sonejita Nayak; Divya Rajawat; Subhashree Parida; G. K. Gaur; Triveni Dutt; Bharat Bhushan (Tropical Animal Health and Production, 2022)

An integrated approach for modeling uncertainty in human health risk assessment - Harshit Mishra; Jitendra Singh; Subhankar Karmakar; Rakesh Kumar (Environmental Science and Pollution Research, 2021)

Benthic Foraminiferal Response to the Millennial-Scale Variations in Monsoon-Driven Productivity and Deep-Water Oxygenation in the Western Bay of Bengal During the Last 45 ka - Komal Verma; Harshit Singh; Arun Deo Singh; Pradyumna Singh; Rajeev Kumar Satpathy; Pothuri Divakar Naidu (Frontiers in Marine Science, 2021)
In this study, we presented a high-resolution benthic foraminiferal assemblage record from the western Bay of Bengal (BoB) (off Krishna–Godavari Basin) showing millennial-scale variations during the last 45 ka. We studied temporal variations in benthic foraminiferal assemblages (relative abundances of ecologically sensitive groups/species, microhabitat categories, and morphogroups) to infer past changes in sea bottom environment and to understand how monsoon induced primary productivity-driven organic matter export flux and externally sourced deep-water masses impacted the deep-sea environment at the core site. Our records reveal a strong coupling between surface productivity and benthic environment on glacial/interglacial and millennial scale in concert with Northern Hemisphere climate events. Faunal data suggest a relatively oxic environment when the organic matter flux to the sea floor was low due to low primary production during intensified summer monsoon attributing surface water stratification and less nutrient availability in the mixed layer. Furthermore, records of oxygen-sensitive benthic taxa (low-oxygen vs. high-oxygen benthics) indicate that changes in deep-water circulation combined with the primary productivity-driven organic matter flux modulated the sea bottom oxygen condition over the last 45 ka. We suggest that the bottom water at the core site was well-ventilated during the Holocene (except for the period since 3 ka) compared with the late glacial period. At the millennial timescale, our faunal proxy records suggest relatively oxygen-poor condition at the sea floor during the intervals corresponding to the cold stadials and North Atlantic Heinrich events (H1, H2, H3, and H4) compared with the Dansgaard/Oeschger (D-O) warm interstadials. The study further reveals oxygen-poor bottom waters during the last glacial maximum (LGM, 19–22 ka) which is more pronounced during 21–22 ka. A major shift in sea bottom condition from an oxygenated bottom water during the warm Bølling–Allerød (B/A) (between 13 and 15 ka) to the oxygen-depleted condition during the cold Younger Dryas (YD) period (between 10.5 and 13 ka) is noticed. It is likely that the enhanced inflow of North Atlantic Deep Water (NADW) to BoB would have ventilated bottom waters at the core site during the Holocene, B/A event, and probably during the D-O interstadials of marine isotope stage (MIS) 3.

Evaluation of precipitation datasets available on Google earth engine over India - Saket Dubey; Harshit Gupta; Manish Kumar Goyal; Nitin Joshi (International Journal of Climatology, 2021)
Monthly mean precipitation estimates of seven products (TerraClimate, TRMM, CHIRPS, PERSIANN‐CDR, GPM‐IMERG, ERA5 and CFSR) available on Google earth engine (GEE) are evaluated against gridded gauge‐based precipitation product available from Indian Meteorological Department (IMD) for their skills and presence of systematic biases (during 2001–2018). All these products represent the climatological features reasonably well. Presence of systematic biases in these products is also observed from their evaluation. Biases across the periphery of the country are relatively on the higher side in comparison to the central regions. The magnitude of spatial variability is represented better for winter precipitation in comparison to summer precipitation. During both winter and summer, ensemble mean of various products outperforms individual products in terms of both RMSE and correlation. Performance of these products is also assessed across various Indian states, elevation bands and climate zones. The ability of these products to represent the seasonality was observed to be highest for the states with mid‐ranged peaks (10–20 mm·day −1 ) which tend to decrease with both increasing and decreasing peaks. Ability of the precipitation products to resemble the annual cycle does not vary with the amount of precipitation, although individual disparity among the products exists. Additionally, an alternative approach for data evaluation using Multiple Triple Collocation (MTC) was performed for the period 2001–2015 using an additional dataset obtained from soil‐moisture‐based rainfall estimates (SM2RAIN). Results from MTC convey that ERA5 performs relatively poor in comparison to the other products for central India followed by CFSR. In brief, the comprehensive evaluation of precipitation products reported herein will act a valuable reference for the researchers as well as decision makers to select the optimal product for their intended application and will inform the users about the various uncertainties in the foundations and specification of these products.

A long-term comparative assessment of human health risk to leachate-contaminated groundwater from heavy metal with different liner systems - Harshit Mishra; Subhankar Karmakar; Rakesh Kumar; Praneeth Kadambala (Environmental Science and Pollution Research, 2018)

A framework for assessment and characterisation of municipal solid waste landfill leachate: an application to the Turbhe landfill, Navi Mumbai, India - Harshit Mishra; Merwan Rathod; Subhankar Karmakar; Rakesh Kumar (Environmental Monitoring and Assessment, 2016)